Protein tyrosine phosphatase 1B regulates fibroblasts proliferation, motility and extracellular matrix synthesis via the MAPK/ERK signalling pathway in keloid. Issue 2 (14th August 2021) - Qian, Leqi; Wang, Qiang; Wei, Chuanyuan; Wang, Lu; Yang, Yanwen; Deng, Xinyi; Liu, Jiaqi; Qi, Fazhi
Abstract: Keloid is a fibroproliferative disorder resulting from trauma, characterized by abnormal activation of keloid fibroblasts and excessive deposition of extracellular matrix (ECM). It affects life quality of patients and lacks of effective therapeutic targets. Protein tyrosine phosphatase 1B (PTP1B) belongs to the protein tyrosine phosphatases and participates in many cellular processes such as metabolism, proliferation and motility. It has been reported that PTP1B negatively regulated diabetic wound healing and tumor progression. However, its effects in keloid remain unclear. Here, we aimed to evaluate the effects of PTP1B on keloid fibroblasts which play essential roles in keloids pathogenesis. Our results revealed that PTP1B expression was decreased both in keloid tissues and in keloid fibroblasts compared to healthy controls. Keloid fibroblasts (KFs) showed higher cell proliferation, motility, ECM production and ERK activity than normal fibroblasts (NFs). Overexpression of PTP1B in KFs and NFs inhibited cell proliferation, motility, ECM synthesis and the MAPK/ERK signalling pathway while knockdown of PTP1B showed converse effects. The rescue experiments with ERK inhibitor further verified that MAPK/ERK signalling pathway involved in PTP1B regulatory network. Taken together, our findings indicated that overexpression of PTP1B suppressed keloid fibroblasts bio‐behaviours and promoted their phenotype switch to normal cells via inhibiting the MAPK/ERK signalling pathway, suggesting it may be a potential anti‐keloid therapy. Abstract : Keloid characterizes by excessive proliferation of fibroblasts, invasive growth beyond the bounders and increased deposition of extracellular matrix (ECM). Overexpressing protein tyrosine phosphatase 1B (PTP1B) in keloid fibroblasts suppressed cell proliferation, motility and ECM synthesis via inhibiting MAPK/ERK signalling pathway. Taken together, PTP1B targets at the key points of keloid pathogenesis, indicating it could be a potential anti‐keloid therapy.